Supporting talents and differentiation in integrated classes - Fellegi, Bálint; Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2014)
Supporting talents and differentiation in integrated classes The aim of this study is to introduce how the activity of talent-support may be extended to the subject of Physics as well; and how the topic could be brought closer to the students who read book seldom, but use computer, internet and smartphones on a daily basis. In this paper an electronic educational program of Physics, named after Edison, will be also introduced. The program can be described as a bridge between games and serous planning, and is suitable for primary and secondary schools both, being able to be adapted to the minimum and the advanced criteria as well. By the means of the game an unique opportunity will open up to differentiate within one classroom and support the promising talents.
Keywords: talent; differentiation; integrated classes; physics education